The Role of Teachers in the Implementation of Online Learning for Third Grade Students in Learning Citizenship Education at Tamansari 2 Yogyakarta Elementary School - Wachid Pratomo; Nadziroh Nadziroh; Chairiyah Chairiyah (JED (Jurnal Etika Demokrasi), 2021)
This study aims to describe the role of teachers in the implementation of online learning for third grade students in learning citizenship education at Tamansari 2 Yogyakarta Elementary School. The method used in this research is descriptive qualitative. The data analysis technique used in this study was an interactive model from Miles and Huberman which consisted of several stages, namely data collection, data reduction, data presentation, and conclusion drawing. The results of the collected data indicate that: The role of teachers in online learning is more in delivering material that is made as attractive as possible so that it is easy to understand and not boring for students. Supporting factors in online learning include providing internet quotas for teachers and students, so that learning that takes place online can continue without any quota constraints. Constraints in online learning are that some parents are lacking in the use of technology, some parents of students with inadequate technology, slow internet is also one of the obstacles in this online learning. Online learning should be given in stages, because not all parents are technology savvy. Efforts to overcome obstacles in the implementation of online learning, before using technology for learning such as google classroom the teacher conducts socialization first so that parents also understand how to use this technology, provide internet quota for teachers and students so that learning goes well. Cooperation between teachers and parents of students is also important, because when the teacher conveys learning to students, the teacher must first provide direction to the parents of students and then to the students. Penelitian ini bertujuan untuk mendeskripsikan peran guru dalam pelaksanaan pembelajaran daring untuk siswa kelas III dalam pembelajaran pendidikan kewarganegaraan di SD Negeri Tamansari 2 Yogyakarta. Metode yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Teknik analisis data dalam penelitian ini peneliti menggunakan model interaktif dari Miles dan Huberman yang terdiri dari beberapa tahapan yaitu pengumpulan data, reduksi data, penyajian data, dan penarikan kesimpulan. Hasil data yang terkumpul menunjukkan bahwa: Peran guru dalam pembelajaran daring lebih banyak menyampaikan materi yang dibuat semenarik mungkin agar mudah dipahami dan tidak membosankan bagi siswa. Faktor pendukung dalam pembelajaran daring antara lain diberikan kuota internet untuk guru dan siswa, sehingga pembelajaran yang berlangsung secara daring dapat terus berjalan tanpa ada lagi kendala kuota. Kendala dalam pembelajaran daring adalah sebagian orang tua siswa kurang dalam penggunaan teknologi, sebagian orang tua siswa dengan teknologi yang kurang memadai, internet yang lambat juga menjadi salah satu kendala dalam pembelajaran daring ini. Pembelajaran daring harus diberikan secara bertahap, karena tidak semua orang tua paham teknologi. Upaya mengatasi kendala dalam pelaksanaan pembelajaran daring, sebelum menggunakan teknologi untuk pembelajaran seperti google classroom guru melakukan sosialisasi terlebih dahulu agar orang tua siswa juga paham bagaimana cara menggunakan teknologi tersebut, memberikan kuota internet untuk guru dan siswa sehingga pembelajaran berjalan dengan baik. Kerja sama antara guru dan orang tua siswa juga penting, karena ketika guru menyampaikan pembelajaran kepada siswa, guru harus memberikan arahan terlebih dahulu kepada orang tua siswa kemudian kepada siswa.